PENGARUH PENGELUARAN PEMERINTAH DAN JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU: PENGARUH PENGELUARAN PEMERINTAH DAN JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU - Julia Sernasari (ECO-BUILD, 2020)
This study aims to determine the effect of economic growth on local original government revenue in Berau Regency. The purpose of this study is to determine the effect of government spending and number of population on economic growth in Berau Regency. This study used economic growth as dependent variable while government spending and number of population as independent variables. The data used in this study was secondary data in the form of annual or time series from 2009 to 2017. While the model used in this study was multiple linear regression. Based on the results it could be concluded that government spending and number of population could affect economic growth by 32 percent. In this study, Berau Regency government expenditure has a significant positive effect on economic growth in Berau Regency. While the number population didn't significantly influence economic growth in Berau Regency.